2022
DOI: 10.1002/jms.4828
|View full text |Cite
|
Sign up to set email alerts
|

Fast and eco‐friendly method using atmospheric solids analysis probe mass spectrometry to characterize orange varieties

Abstract: Orange fruit is one of the most popular types of fruit in the world, and its juice is the main product of its processing. This study aimed to evaluate a simple, fast, and eco-friendly methodology, atmospheric solids analysis probe mass spectrometry (ASAP-MS), to assess the chemical profile of four oranges varieties (Valencia, Folha Murcha, Pera, and Iapar). The oranges' varieties were evaluated for the physicochemical composition (extraction yield, pH, total titratable acidity, total soluble solids [TSS], Br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…For example, mass spectral profiles recorded under ASAP conditions in conjunction with principal component analysis (PCA) have been recommended as a protocol for routine analysis to monitor the varieties of the oranges. 16 This study and other previous investigations 18,51,52 have demonstrated that mass spectral profiles acquired under plasma-ionization conditions are highly affected by the nature of vapor molecules present in the ion source enclosure. Therefore, it is vital that ambient conditions are carefully monitored and controlled when ASAP and other ambient ionization methods are used for sample profiling.…”
Section: ■ Conclusionmentioning
confidence: 51%
See 2 more Smart Citations
“…For example, mass spectral profiles recorded under ASAP conditions in conjunction with principal component analysis (PCA) have been recommended as a protocol for routine analysis to monitor the varieties of the oranges. 16 This study and other previous investigations 18,51,52 have demonstrated that mass spectral profiles acquired under plasma-ionization conditions are highly affected by the nature of vapor molecules present in the ion source enclosure. Therefore, it is vital that ambient conditions are carefully monitored and controlled when ASAP and other ambient ionization methods are used for sample profiling.…”
Section: ■ Conclusionmentioning
confidence: 51%
“…Moreover, the overall method has provided an analytical protocol for the identification of pollen samples as well . In a recent study, ASAP-MS in conjunction with principal component analysis (PCA) has been employed to characterize orange juice varieties …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ASAP was applied, for example, to classify tea varieties or for the authentication of Manuka honey concerning brand protection [90,91]. Further studies with ASAP aimed to detect pharmaceutical drugs that are illegally added to functional food [92] and to differentiate between various vegetable oils or orange varieties [93,94].…”
Section: Ionization Sourcesmentioning
confidence: 99%
“…In addition, it is efficient of ionizing low polarity molecules not responsive to ESI‐MS and atmospheric pressure chemical ionization (APCI) at high sensitivity 16 . The ASAP‐MS was applied to the rapid analysis of oranges, 17 cereals, 18 airborne particles, 13 petroleum, 16 and vegetable oils 19 . However, to the best of our knowledge, no study has evaluated the quality and purity of body oils containing sweet almond oil in their composition using ASAP‐MS.…”
Section: Introductionmentioning
confidence: 99%